Fault Location Scheme for Abnormal Grounding Point in Isolated Ground Wire of Large-Scale Clean Energy Transmission - Wang, Yunlong; Chen, Nuo; Ma, Xiangnan; Yang, Zongzhang (Frontiers in Energy Research, 2021)
There is a large number of grounding switches along the isolated ground wire for the de-icing in the large-scale wind farm. If any of these grounding switches are left open by accident, this can create an unexpected abnormal grounding point in the isolated ground wire. Based on the analysis of the output power of de-icing devices, the output power of different poles can be applied for the abnormal grounding point fault location. Since the rise of output current to the rated current of de-icing devices requires a long time to build up, the protective relay may lock the de-icing device before the output current reaches the rated current. Thus, the ratio of output energy of two poles can be selected to locate the abnormal grounding point. This study verified this location method by conducting a large number of simulations.